Penyusunan Laporan Keuangan Pada UMKM Kelurahan Tangkerang Tengah Kecamatan Marpoyan Damai Kota Pekanbaru - Zubir Zubir; Candra Irawan; Sabrina Khairannisa; Rahmadewi Rezki; Tri Maharani; Vellya Sandela; M. Sohar Afandi (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2022)
MSMEs play an important role in economic growth. There are several problems faced by MSMEs at this time including difficulties in marketing, limited innovation, and technology, as well as limited knowledge about making financial statements. In order to increase interest in the importance of knowledge about financial statements, These community service activities are very necessary at this time. The method of devotion is done by giving Lectures, Discussions, and Mentoring. As the results of this activity, MSME actors already understand how to make financial statements, namely balance sheets and income statements